Pregnancy after drug-free in vitro activation of follicles and fresh tissue autotransplantation in primary ovarian insufficiency patient: a case report and literature review - F. Fabregues; J. Ferreri; J.M. Calafell; V. Moreno; A. Borrás; D. Manau; F. Carmona (BMC, 2018)
Abstract Background The aim of this report was to describe a case of pregnancy after drug-free in vitro activation (IVA) of follicles and fresh tissue autotransplantation in primary ovarian insufficiency (POI) patient and to review the pertinent literature. Methods We present a case in wich a 32 - years old patient with POI became pregnant after IVA without tissue culture and with ovarian tissue transplantation. We also reviewed the literature using Pubmed database. Case presentation Pretreatment with estradiol/progesterone stopped the day before surgery. The removal of the ovarian cortex and autotransplantation were performed by laparoscopy in the same surgical act. Ovarian fragments were transplanted in contralateral ovary and peritoneal pocket near to the ovary. Immediately after surgery GnRH agonist together HMG injections started, leading the growth of 3 preovulatory follicles and the retrieval of two mature eggs. After IVF two embryos were transferred and singleton pregnancy was established and currently she is 25 weeks pregnant. Results A total of 51 patients with POI in whom an in vitro activation of ovarian tissue was performed, were collected from the revieew of the literature. In 29.4% of them, follicular development was obtained and in 4 of them a pregnancy. In all of them, a combined technique (fragmentation and activation) was performed in two laparoscopies. No case has been reported successfully after drug-free in vitro activation. Conclusions This is the first report about a case with pregnancy after drug-free in vitro activation of follicles and fresh tissue autotransplantation in POI patient.